Assessment of the competitiveness of the tourist destination - O. Chernega (Economics, Entrepreneurship, Management, 2021)
The tourism industry, which has shown exceptionally high rates of development in recent decades in the world economy, allows tourist destinations, which usually have limited resources for industrial development, to achieve income levels in industrialized regions, and with a balanced and effective government policy even overcome the effects of socio-economic crises. One of the conditions for the successful existence of a tourist destination is the need to constantly monitor the level of its competitiveness by various criteria to identify strengths and weaknesses and, accordingly, to develop tactics and strategies for the development of the industry at different levels of management. The main criteria for the competitiveness of the destination is the compliance of the main tourist product of the territory to the needs of consumers. Various methods are used to assess the potential of tourist destinations, based on the defined capacity of the territories and the relationship to its potential, the load on resources and infrastructure, the definition of climatic, natural locations, economic indicators, etc. The definition of methods as a result of competitive analysis is the basis for building a reputable strategy for the development of the destination and subsequent vectors of positioning and the tourist world arena. Namely, it is expressed in the fact that as a result of the measures taken to manage the reputation management of the tourist destination, the competitive environment improves, the market develops, the infrastructure improves, which leads to the competitiveness of the tourist destination